Differential Effects of Self-Reported Lifetime Marijuana Use on Interleukin-1 Alpha and Tumor Necrosis Factor in African American Adults - Keen, Larry (J Behav Med, 2015)
It is unknown how lifetime marijuana use affects different proinflammatory cytokines. The purpose of the current study is to explore potential differential effects of lifetime marijuana use on interleukin-1 alpha (IL-1α) and tumor necrosis factor (TNF) in a community based sample. Participants included 168 African American adults (51% female, median age= 47 years). Upon study entry, blood was drawn and the participants completed questions regarding illicit drug use history whose answers were used to create three groups: lifetime non-drug users (n= 77), lifetime marijuana only users (n= 46) and lifetime marijuana and other drug users (n= 45). In the presence of demographic and physiological covariates, non-drug users were approximately two times more likely (AOR= 2.73, CI= 1.18, 6.31; p= .03) to have higher TNF levels than marijuana only users. Drug use was not associated with IL-1α. The influence of marijuana may be selective in nature, potentially localizing around innate immunity and the induction of cellular death.